The Relationship between Dagusibu's Knowledge Level and Understanding of Antibiotic Use in the Community in North Denpasar District - Kadek Mirah Triyade Suwena; Putu Eka Arimbawa; I Gusti Agung Haryawan (Yayasan Baru Haji Samsudin, 2024)
85.9% of urban and rural communities do not have proper knowledge about medicines. This causes problems related to the use of drugs, one of which is antibiotics, which will cause antibiotic resistance. Resistance is the greatest threat facing the world, causing more deaths than cancer. Southeast Asia has the highest number of such cases in the world. Knowing the relationship between DAGUSIBU knowledge level and understanding of the use of antibiotics in the community in North Denpasar District. This research is a quantitative observational study with a cross sectional design. sampling using the method (Non-Probability Sampling) with a purposive sampling technique, as many as 400 respondents, with an age range of 17-64 years. The instrument used is a knowledge and understanding questionnaire that has been tested for validity and reliability. The data obtained were analyzed with SPSS with the Spearman rank method. Level of knowledge classified as high 64%, low 35.8%. Understanding of the use of antibiotics classified as understanding 52.3% and not understanding 47.8%. The results of the Rank Spearman correlation test show a correlation coefficient of 0.582 with a significance value of 0.001 (p <0.05), meaning that there is a significant relationship with a fairly strong correlation coefficient. There is a fairly strong and positive or unidirectional relationship between the knowledge level of DAGUSIBU and the understanding of the use of antibiotics in the community in North Denpasar District